Social philosophy and sociology: the problem of disciplinary boundaries - Gafarov, Hassan S.; Gafarova, Julia J. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
The article is devoted to the problem of disciplinary self-determination in social philosophy. The main stages of the process of self-determination are shown discretely. The authors demonstrate as the problematic of the social becomes actual again in the end of the XIX century in the polemics of neo-Kantianism, Marxism and neo-Hegelianism. They describe as in 1920–1930s the social becomes at last an independent field of research. The authors conclude that, underlining the axiological problematic of «good life», social philosophy comes in the opposition with sociology on the field of the dichotomies like empirical and metatheoretical, is and ought, descriptive and normative.
Keywords: social philosophy; sociology; social; self-determination; disciplinary self-determination; empirical; theoretical; descriptive; normative; «good life»